Dynamical chaos : proceedings of a Royal Society discussion meeting held on 4 and 5 February 1987 - Berry, Michael V.; Percival, Ian, 1931-; Weiss, N. O. (Nigel Oscar) (Princeton legacy library., 1987)
The leading scientists who gave these papers under the sponsorship of the Royal Society in early 1987 provide reviews of facets of the subject of chaos ranging from the practical aspects of mirror machines for fusion power to the pure mathematics of geodesics on surfaces of negative curvature. The papers deal with systems in which chaotic conditions arise from initial value problems with unique solutions, as opposed to those where chaos is produced by the introduction of noise from an external source. Table of Contents Diagnosis of Dynamical Systems with Fluctuating Parameters D. Ruelle Non.